INTERESTING FEATURES OF FEMALE DROMEDARY (CAMELUS DROMEDARIUS) REPRODUCTION - PUROHIT, G N; VYAS, SUMANT; SARSWAT, CHANDRASHEKHER; KUMAR, AMIT; DHOLPURIA, SANDEEP (The Indian Journal of Animal Reproduction, 2023)
Inormation on the reproduction in camel continues to be poorly known and scattered. Some interesting features include seasonality of breeding, delayed puberty, peculiar anatomy of the reproductive structures, poorly defined estrus and estrous cycle and induced nature of the ovulation. Other interesting features include exclusive left uterine horn pregnancy, faster demise of the corpus luteum in the absence of pregnancy, an early maternal recognition of pregnancy, upward curling of tail (tail cocking) by Day 15 of pregnancy, diffuse placenta and a longer gestation period of 12-13 months. This review collates scientific data on the above interesting features of female camel reproduction.